Electrochemical oxidation/reduction of selected compounds mediated by indium tin oxide doped with lithium and glassy carbon electrode modified with tin dioxide - Yeo, May Ching (2012)
The new chemically modified electrodes based on indium tin oxide (ITO) doped with lithium (Li+/ITO) and tin oxide modified glassy carbon electrode (SnO2/GCE) were fabricated by potential cycling and mechanical attachment methods, respectively. The Li+/ITO electrode and SnO2/GCE has been characterized using voltammetric techniques of cyclic voltammetry, chronoamperometry and chronocoulometry in this work. The Li+/ITO electrode was applied in the electrochemical determination of 50 μM Mn(II) in 0.1 M KCl (pH 6.9) and 50 μM Hg(II) in 0.1 M KCl (pH 6.4). The current enhancements of 2.9 times for the reduction of Mn(II) and 2.7 times for the reduction of Hg(II) were obtained by using the Li+/ITO electrode compared to unmodified ITO electrode. Under the optimized parameters, the linear calibration graph showed correlation coefficient of 0.992 for the reduction of 10 μM to 1.0 mM Hg(II) and 0.995 for the concentration isotherm of Mn(II) in the range of 10 μM to 1.0 mM, with a linearity up to 0.2 mM. From this calibration plot, high sensitivity response of 2298.1 μA/mM with detection limit of 78.3 nM for the reduction of Hg(II) and 1777.3 μA/mM with detection limit of 100 nM for the reduction of Mn(II) at the Li+/ITO electrode were obtained Effect of scan rate of Hg(II) and Mn(II) was studied in the range of 5 mV/s to 200 mV/s, and linear relation was observed. Based on the plot of log reductive current vs. log scan rate, experimental slopes of 0.38 and 0.84 were obtained for Hg(II) and Mn(II) respectively, indicating that the reaction under diffusion controlled and surface complex reaction respectively. Diffusion coefficient was calculated as 5.75x10-6 cm2/s and 2.54x10-7 cm2/s from the chronocoulometry study, and the activation energy obtained was 20.79 kJ/mol and 12.42 kJ/mol for Mn(II) and Hg(II) respectively in aqueous media at the Li+/ITO electrode. Excellent analytical and recovery rates have been obtained using either lake or sea water samples spike with the analyte. Besides, the bulk SnO2/GCE was used for the electrochemical determination of 1.0 mM of ascorbic acid in 0.1 M KCl (pH 5), whereas spherical SnO2/GCE was applied in the electrochemical determination of 1.0 mM of Hg(II) in 0.1 M KCl (pH 7.4). The current enhancements of 1.4 times for the oxidation of ascorbic acid and 1.5 times for the reduction of Hg(II) were also obtained by using bulk SnO2/GCE and spherical SnO2/GCE respectively compared to bare GCE. Calibration plot reveals linearity from the range of 20 μM to 2.0 mM with a correlation coefficient of 0.993 for the detection of ascorbic acid and concentration isotherm of Hg(II) in the range 0.5 μM to 1.0 mM, with linearity of up to 10 μM with a correlation coefficient of 0.999. The sensitivity and detection limit was estimated to be 23.47 μA/mM and 2.5 μM respectively for ascorbic acid and 61.79 μA/mM and 75 nM respectively for Hg(II). Furthermore, the diffusion coefficient and activation energy of ascorbic acid using bulk SnO2/GCE were estimated to be 8.09 x 10-9 cm2/s and 14.26 kJ/mol respectively while the values of the diffusion coefficient and activation energy of Hg(II) using spherical SnO2/GCE were 2.84x10-6 cm2/s and 21.66 kJ/mol respectively. Practically, SnO2 modified GC electrode could be used for the determination of ascorbic acid in rose syrup sample and Hg(II) in sea water sample. Therefore, the use of Li+/ITO electrode and SnO2/GCE are highly sensitive, selective and stable in electrochemical measurement. In addition, the surface morphology of the Li+/ITO electrode and SnO2 film before and after electrolysis was studied by scanning electron microscopy (SEM) and the percentage of the elements in components was examined by energy dispersive X-ray (EDX). Both of the SEM and EDX evidences that the Li+/ITO electrode and SnO2 film before and after electrolysis are solid to solid conversion.